2013
DOI: 10.3748/wjg.v19.i42.7412
|View full text |Cite
|
Sign up to set email alerts
|

Is increased red cell distribution width an indicating marker of nonalcoholic steatohepatitis and fibrotic stage?

Abstract: RDW a new non-invasive marker that can be used to demonstrate the presence of NASH and indicate advanced fibrotic scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
1
27
0
6
Order By: Relevance
“…There has been evidence that the RDW may predict mortality in newly hospitalised patients, critically ill patients and in older community patients [4,[22][23][24][25], with RDW also a marker of diabetes in the elderly through a HbA1c association [26]. Increased RDW also may be a useful marker for the assessment of liver function, with associations noted for both non-alcoholic steatohepatitis and fibrosis [27], and HBV induced liver cirrhosis [28]. Underpinning RDW associations with the diverse array of disease is a likely link to increased inflammation [3,29] and disrupted erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…There has been evidence that the RDW may predict mortality in newly hospitalised patients, critically ill patients and in older community patients [4,[22][23][24][25], with RDW also a marker of diabetes in the elderly through a HbA1c association [26]. Increased RDW also may be a useful marker for the assessment of liver function, with associations noted for both non-alcoholic steatohepatitis and fibrosis [27], and HBV induced liver cirrhosis [28]. Underpinning RDW associations with the diverse array of disease is a likely link to increased inflammation [3,29] and disrupted erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…These scores consist of easily available and applicable variables, such as aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AAR), AST to platelet ratio index (APRI), fibrosis index (FI), fibrosis cirrhosis index (FCI), and fibrosis 4 (FIB‐4) score . As there is a growing necessity of non‐invasive markers in predicting fibrosis, various markers have been reported to be associated with liver fibrosis, although there is a clear lack in this field …”
Section: Introductionmentioning
confidence: 99%
“…Elevated RDW has been reported to associate with higher mortality risk among the general population (39). Cengiz et al (40) have also reported a positive correlation between RDW values and fibrotic scores in patients with NASH. Hu et al (41) have observed that RDW increased in chronic patients with CHB and have suggested that RDW may serve as a potential prognostic index in liver disease.…”
Section: Discussionmentioning
confidence: 86%